Supernatural. Season fifteen [videorecording (DVD)] - Padalecki, Jared, 1982-; Ackles, Jensen; Collins, Misha; Calvert, Alexander (Warner Home Video, 2021)
The epic journey of the Winchester brothers ends in the fifteenth and final season. Sam, Dean, and Castiel have battled the forces of darkness in an unending quest to save the world. But in the season fourteen finale, they faced off against God Himself, refusing to kill their surrogate son Jack, and thus bringing about God's decision to end this reality once and for all.